Marginal structural modelling of associations of occupational injuries with voluntary and involuntary job loss among nursing home workers. Issue 3 (19th January 2016) - Okechukwu, Cassandra Adiba; Bacic, Janine; Velasquez, Esther; Hammer, Leslie B
Abstract : Objectives: Qualitative studies have highlighted the possibility of job loss following occupational injuries for some workers, but prospective investigations are scant. We used a sample of nursing home workers from the Work, Family and Health Network to prospectively investigate association between occupational injuries and job loss. Methods: We merged data on 1331 workers assessed 4 times over an 18-month period with administrative data that include job loss from employers and publicly available data on their workplaces. Workers self-reported occupational injuries in surveys. Multivariable logistic regression models estimated risk ratios for the impact of occupational injuries on overall job loss, whereas multinomial models were used to estimate OR of voluntary and involuntary job loss. Use of marginal structural models allowed for adjustments of multilevel lists of confounders that may be time varying and/or on the causal pathway. Results: By 12 months, 30.3% of workers experienced occupational injury, whereas 24.2% experienced job loss by 18 months. Comparing workers who reported occupational injuries to those reporting no injuries, risk ratio of overall job loss within the subsequent 6 months was 1.31 (95% CI 0.93 to 1.86). Comparing the same groups, injured workers had higher odds of experiencing involuntary job loss (OR 2.19; 95% CI 1.27 to 3.77). Also, compared with uninjured workers, those injured more than once had higher odds of voluntary job loss (OR 1.95; 95% CI 1.03 to 3.67), while those injured once had higher odds of involuntary job loss (OR 2.19; 95% CI 1.18 to 4.05). Conclusions: Despite regulatory protections, occupational injuries were associated with increased risk of voluntary and involuntary job loss for nursing home workers.